Critical role of relationship for unfamiliar banking products - DURMUŞ, BERİL (BILGESEL YAYINCILIK SAN & TIC LTD, 2013)
This paper aims to explore factors affecting the decision making of consumers for investing in unfamiliar banking products. Capital protected funds are the subject of this study. The study analyses the consumers' investment in capital protected funds and its preceding factors among 160 bank consumers in Turkey selected judgmentally. The data of this descriptive study is collected by a structured questionnaire. Revisiting the relevant literature, four constructs (consumer's perceived service quality of customer relationship manager; consumer's perceived brand trust, consumer's risk tolerance and consumer's financial literacy) were analyzed to be the main factors affecting capital protected fund investment. The results show that perceived service quality of customer relationship managers is the only significant factor affecting the investment in capital protected funds. As an implication, banks should invest on customer relationship management policies emphasizing the optimization of customer relationship managers' service quality levels.
Keywords: Capital Protected Funds; Structured Products; Service Quality; Brand Trust; Risk Tolerance; Financial Literacy; SERVICE QUALITY; INDEX CERTIFICATES; TRUST; SCALE; MODEL; MARKET